KEJADIAN DEPRESI PADA REMAJA MENURUT DUKUNGAN SOSIAL DI KABUPATEN JEMBER: Depression Incidence in Adolescents According to Social Support in Jember Regency - Adi Zayd Bintang; Ayik Mirayanti Mandagi (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2021)
ABSTRACTDepression is a mental health problem that mostly occurs during adolescence. Physical, cognitive and emotional changes experienced during adolescence can cause stress. The prevalence of depression in adolescence has a very high increase compared to the age of children and adults. The main factor in being able to cure depression in adolescents is social support (Depkes, 2007). This study aims to identify depressive symptoms in adolescents and to find out the relationship between social support factors and depression incidence. This research is a quantitative research, with the type of observational analytic research with a cross sectional approach involving students at SMA XY in Jember Regency in May 2020. The analytical method uses the Chi Square test to see the relationship between independent and dependent variables with a significance level of Î± â‰¤ 0, 05. Data collection tool using google form. Determination of respondents by random sampling with a total of 158 respondents. The results of this study indicate that the distribution of women is 76.58% more than that of men. Based on the distribution of social support, 56.96% received good social support, while based on the incidence of depression, 54.43% did not experience depression. From the statistical test, the significance value of <0.05 indicates that there is a relationship between social support factors and the incidence of depression. Social support plays an effective role in overcoming depression experienced by adolescents.Keywords: Depression, Teens, social support. ABSTRAKDepresi merupakan salah satu masalah kesehatan mental yang sebagian besar terjadi pada masa remaja. Perubahan fisik, kognitif dan emosional yang dialami pada masa remaja dapat menimbulkan stress. Prevalensi depresi pada usia remaja memiliki peningkatan yang sangat tinggi dibandingkan dengan usia anak-anak dan usia dewasa. Faktor utama untuk dapat menyembuhkan depresi pada remaja yaitu dukungan sosial (Depkes, 2007). Penelitian bertujuan untuk mengidentifikasi gejala depresi pada remaja dan mengetahui mengenai Hubungan Faktor Dukungan Sosial dengan Kejadian Depresi. Penelitian ini adalah penelitian kuantitatif, dengan jenis penelitian analitik observasional dengan pendekatan cross sectional yang melibatkan siswa di SMA XY di Kabupaten Jember pada Bulan Mei tahun 2020. Metode analisis menggunakan uji Chi Square untuk melihat hubungan variabel independen dan dependen dengan tingkat kemaknaan Î± â‰¤ 0,05. Alat pengumpulan data menggunakan google form. Penentuan responden secara random sampling dengan jumlah 158 reponden. Hasil penelitian ini menunjukan distribusi perempuan 76,58% lebih banyak daripada laki-laki, berdasarkan distribusi dukungan sosial sebesar 56,96% mendapatkan dukungan sosial yang baik, sedangkan berdasarkan kejadian depresi sebesar 54,43% tidak mengalami depresi. Dari uji statistik nilai signifikansi sebesar < 0,05 menunjukkan bahwa ada hubungan antara faktor dukungan sosial dengan kejadian depresi. Dukungan sosial berperan efektif dalam mengatasi depresi yang dialami remaja.Kata Kunci: Depresi, Remaja, Dukungan Sosial.